Globalizing the Latin American legal field: Continental and regional approaches to the international legal order in Latin America - Scarfi, Juan Pablo (2018)
Through an analysis of the international legal thought of Alejandro Alvarez, Ruy Barbosa, Isidro Fabela and Carlos Saavedra Lamas, this paper shows that Latin America played a vital and complex role in the reconfiguration of a new global legal order in the early twentieth century and the consolidation of the modern discipline of international law, as well as a specific legal field in Latin America. It argues that the region was a pioneer in the promotion of distinctive continental and regional approaches to international law and world peace before and after the creation of the League of Nations.